Trends in Budgeting in the Education Sector of Nepal - Joshi, Bishnu Maya (Interdisciplinary Research in Education, 2023)
This paper analyzes the trends in budgeting in the education sector of Nepal. Budget allocation trends are essential in the education sector for ensuring equality, improving education quality, enhancing accountability, and guiding policy decisions. This paper argues that investment in education is indispensable for national development. To fulfill this objective, the trends in budget allocation in the education sector support working among the stakeholders to ensure access to quality education. This paper is based on reviews of documents related to the ten-year budget allocation practices of the government of Nepal from 2012–13 to 2022–23. Other documents were collected from archived records and e-resources from Google. The finding reveals that the trends in total budget allocation have been increasing year by year, while the annual budget in the education sector remains eleven percent of its total budget in these periods. This paper concludes that fifteen percent of the total budget is required to attain Sustainable Development Goal 4. Thus, the government should increase its budget in the education sector to fulfill the commitment of the signatory state in various international forums.